(untitled) (International Journal of Innovative Research in Engineering & Management, 2022)
The world’s population is becoming more environmentally conscious, and as a result, regulations governing the management of industrial waste are becoming more stringent. As a result, the world’s attention is increasingly being directed toward researching the properties of industrial waste and finding solutions on how to make use of the waste’s valuable component parts. This is done in the expectation that these priceless component components can be repurposed for use as secondary raw material in one or more other types of industrial applications. This report demonstrates that it is possible to use iron slag as a partial replacement for sand and silica fume as a partial replacement of cement in concrete. This is accomplished by taking into account the specificity of the physical and chemical properties of these products. In addition, the report also takes into account the optimized content of these two materials. An investigation into the mechanical properties is provided. According to the findings, the strength attributes of concrete significantly improve when iron slag and silica fume are used to partially substitute for sand and cement in the optimized combination.